Quality management for competitive advantage in global markets - Sáiz Álvarez, José Manuel; Olalla-Caballero, Beatriz, 1978- (Advances in business strategy and competitive advantage., 2021)
"This book discusses the importance of quality practices and global market practices. With research that allows practitioners to improve their understanding of the strategic role of quality in the information and knowledge society, it focuses on describing a global economy formed by networks, organizations, teams, workgroups, information systems, and finally, actors in networked environment"--